Learning Algebra in Junior High School Through Drill and Practice Method with Game Approach on Cymath Application Development - Irvan; Zainal Azis; Rina Ardillah Lubis (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
Students have difficulty learning algebra, so they need help to solve it. The biggest challenge students usually face in learning algebra is understanding the concept of variables, equations, and symbolic manipulation. This study aims to analyze the effectiveness of the practice and practice method with a game approach through the Cymath application in learning algebra in junior high schools. This study used a pretest-posttest experimental design with a control group. The sample consisted of 50 students divided into an experimental group of 30 who used the Cymath application and a control group of 20 who did not use the application. The data collection method used a test. The data collection instrument used a test question sheet. Data analysis testing was carried out using the SPSS software version.27 using Kolmogorov-Smirnov and Shapiro-Wilk test statistics for normality, homogeneity, and independent sample T-test tests. The data analysis results showed a significant difference between the experimental group and the control group in terms of improving understanding of algebraic concepts. The experimental group had a standard deviation, which indicated that the scores of students in this group were more centered around the average value. It is concluded that the training and practice method with a game approach through the Cymath application can improve learning outcomes in algebra material.